Daily Spiritual Experience dan Kesejahteraan Psikologis pada Istri yang Kehilangan Pasangan karena Meninggal Dunia - Annisa Parila; Endah Puspita Sari; Wardah Roudhotina (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2018)
The purpose of this study is to determine the correlation between psychological weel-being and daily spritual exprience among widow. there were 45 participants from live villages in Kecamatan Rambah, Rokan Hulu, Riau. Psychological well-being scale was used to collect data and adapted from psychological well being scales by Ryff (1995). Daily spiritual experience scale was used and adapted from daily spiritual experience scales by Underwood and Teresi (2002). The result showed that there is a positive correlation between psychological well-being and daily spiritual experince among widow (r=0.389, p<0.01).